Subject Matter of Special Teacher (Defectology) Specialists’ Training in the AAC Field in Russia and Abroad - Kozlova, K.M. (Autizm i narušenie razvitiâ, 2025)
Objectives. With the adoption of the teacher-defectologist occupational standard in Russia, it has become increasingly relevant to define the subject matter of professional training in the field of alternative and augmentative communication (AAC). This study analyzes the content of higher professional education programs for defectology specialists in the AAC field in Russia and abroad and identifies key characteristics. Methods. A content analysis was conducted on 66 professional training programs in special education, speech-language pathology, and audiology across eight countries. The programs were retrieved from the official websites of educational institutions. The search was performed using Yandex and Google search engines with the keywords: AAC, alternative and augmentative communication, nonverbal communication, nonverbal, communicating. The relevance of the search results was assessed to ensure accuracy. Results. Training in the AAC field is most commonly found in bachelor's degree programs (57% abroad, 56% in Russia) and is distributed across training profiles as follows: speech and language pathology - 39%, special education - 22% (abroad); work with ASD-personalities and logopaedics - 23%, preschool defectology - 18% (in Russia). Some common topics are found in educational programs across different countries, such as AAC teaching strategies. However, other topics differ significantly or are only covered in a limited number of programs. Conclusions. The obtained data allow us to speak about the insufficient representation of disciplines devoted to AAC (such as «Introduction to alternative and augmentative communication», «Learning technology of alternative and augmentative communication » and etc.) in the professional training programs of the special needs teachers. Additionally, there is a need for further selection and structuring of curriculum content in the AAC field to enhance teacher training programs. Актуальность и цель. В связи с принятием в России профессионального стандарта педагога-дефектолога актуальным становится определение содержания подготовки этих специалистов в области альтернативной и дополнительной коммуникации (АДК). Проведен анализ и выявлены особенности содержания высшего профессионального образования специалистов дефектологического профиля в области АДК в России и за рубежом. Методы и методики. Методом контент-анализа проанализированы 66 программ профессиональной подготовки в области специального образования, речеязыковой патологии и аудиологии в 8-ми странах. Исследовались программы, размещенные на официальных сайтах образовательных организаций. Поиск осуществлялся с помощью поисковой строки в поисковых системах Яндекс и Google по ключевым словам: ААС, alternative and augmentative communication, nonverbal communication, АДК, альтернативная и дополнительная коммуникация, невербальный, общение. Результаты поисковой выдачи проверялись на релевантность запросу. Результаты. Наиболее часто дисциплины или темы, посвященные АДК, встречаются в учебных планах и рабочих программах бакалавриата (57% за рубежом, 56% в России) и по профилям подготовки: речеязыковая патология - 39%; специальное образование - 22% (за рубежом); работа с лицами с РАС и логопедия - 23%, дошкольная дефектология - 18% (в России). Ряд вопросов, рассматриваемых в содержании дисциплин, являются общими для разных стран (например, стратегии обучения АДК), некоторые отличаются или представлены в малом количестве программ. Выводы. Полученные данные позволяют говорить о недостаточной представленности дисциплин, раскрывающих теоретические и практические вопросы обучения АДК (например, «Введение в альтернативную и дополнительную коммуникацию», «Технологии обучения альтернативной и дополнительной коммуникации» и т.п.), в программах профессиональной подготовки учителей-дефектологов. Также результаты свидетельствуют о необходимости дальнейшей работы по отбору и структурированию содержания программ подготовки педагогов-дефектологов в области АДК.